Pengaruh Daya Tarik dan Aksesibilitas terhadap Keputusan Berkunjung ke Telaga Biru Cisoka, Kabupaten Tangerang, Provinsi Banten - Marie, Andhalia Liza (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2024)
This research aims to analyze the influence of attractiveness and accessibility on the decision to visit Telaga Biru Cisoka. The method used is a quantitative approach with a survey design, where questionnaires were distributed to 200 tourist respondents. Validity and reliability tests show that the research instruments are reliable. The results of the coefficient of determination analysis show that 52.6% of the variation in visiting decisions can be explained by attractiveness and accessibility, with a significant influence from these two variables. Attractions, which include both natural beauty and man-made attractions, are proven to increase visitor interest, while good accessibility reduces travel barriers, increasing comfort. Based on these results, suggestions for managers include improving facilities and accessibility, as well as adding new features to attract more visitors. In addition, visitors are expected to plan their visits well and share their positive experiences via social media. In conclusion, the combination of strong attractiveness and adequate accessibility plays a major role in tourists' decisions to visit Telaga Biru Cisoka, which has the potential to support tourism growth and the local economy. Keywords: attractiveness, accessibility, decision to visit